DYNAMIC HIP SCREW FIXATION VS. PROXIMAL FEMUR NAIL FOR UNSTABLE PER-TROCHANTERIC FRACTURES: A COMPARATIVE ANALYSIS OF OUTCOMES AND COMPLICATIONS - Memon, Kashif; Siddiqui, Athar Muneeruddin; Khan, Zainab Aqeel; Zahoor, Al Wardha (Journal of Ayub Medical College Abbottabad, 2021)
Background: There are various implant choices to fix unstable per- trochanteric fractures.Theaim of this study was to compare the outcomes of dynamic hip screw and proximal femur nail for unstable per-trochanteric fractures including complications associated with both fixations. Methods: A retrospective analysis done on pertrochanteric fractures of femur who were treated with Dynamic hip Screw (DHS) and Proximal Femur Nail (PFN). The data was taken from our hospital hip data base for the past two years from January 2017 to January 2019. Data of 174 patients was analysed, divided in to Group A with DHS (n=122) and Group B with PFN (n=52). Follow up included X-ray (anteroposterior and lateral) views for fracture union and collapse, femur neck shortening, implant position and identification of mode of failure or collapse (cut out risk) by using tip-apex distance. The Harris hip score used to evaluate mobility status and other functional outcomes.Result: The mean age in years of patients treated with PFN and DHS were 55.9 and 59.8, ranging from 39-83 years. The mean of Harris hip score at 2 year was 69.28±9.99 in DHS group and 72.12±9.71 in PFN group with the p-value 0.31. The mean of limb shortening was 12mm in DHS and 9mm in PFN group. In DHS group, four cases had tip-apex distance of 39 mm and reported implant cut out that needs revision of surgery.Conclusion: Proximal Femur Nailgroup demonstrated no implant cut out and less mean limb length shortening whereas other parameter like functional outcomes, fracture union, rate of infection, hospital stay and postoperative pain are not significantly different in two groups. Keywords: Per trochanteric fracture;Dynamic hip screw;Proximal femur nail;Functional outcomes